A case of anterior scleritis in association with posterior scleritis – a diagnostic riddle - Dastidar, Aditi Ghosh; Goel, Sugandha; Kundu, Debi; Biswas, Jyotirmoy; Nigam, Eesh; Sharma, Preeti (GMS Ophthalmology Cases, 2022)
We herein report a case of a young female presenting with multiple nodular scleral abscesses mimicking infective scleritis with exudative retinal detachment. Repeated diagnostic scraping for microbiological and histopathological analysis was inconclusive. The patient’s systemic and collagen disease work-up was non-contributory. She was treated with multiple surgical debridement and de-roofing of the abscesses along with antibiotic irrigation. Topical and oral steroid was stopped on worsening of the condition, and the patient was maintained on topical and oral antibiotics. Complete resolution of scleritis and exudative detachment was noted at 1 month follow-up and no recurrence was noted until 6 months.